Channel‐Rich Pt0.23Mn0.42Ni0.35 Ternary Alloy Nanocatalysts for Efficient Hydrogen Evolution. Issue 17 (8th September 2022) - Zeng, Biao; Sheng, Hongbin; Cao, Lixin; Dong, Bohua
Abstract: The development of highly active and durable electrocatalysts with low Pt content for key reactions (hydrogen evolution reactions) in acidic electrolyte environments is desirable but remains an open challenge for clean and efficient energy conversion. Here, homogeneous, and unique Pt0.23 Mn0.42 Ni0.35 flower‐like nanostructure were firstly synthesized by a simple low‐temperature oil‐phase strategy. These Pt0.23 Mn0.42 Ni0.35 catalysts exhibit a significantly increased electrochemically active surface area and excellent electrical conductivity due to their alloy nature, uniform, and unique channel‐rich morphological characteristics. The new‐type catalyst shows an ultra‐small overpotential of 23 mV at a current density of 10 mA cm −2, high mass activity (7.61 A mg −1 Pt at −0.07 V) and excellent stability in acidic media. Abstract : Pt0.23 Mn0.42 Ni0.35 catalysts with uniform and unique flower‐like nanostructures exhibit significantly increased catalytic activity and excellent stability due to their alloying nature and distinctive channel‐rich morphological features.